KAPOSI´S SARCOMA - A CLINICOPATHOLOGICAL REVIEW - Resende, Cristina (2015)
Introduction: Kaposi's sarcoma (KS) is a systemic disease, whose neoplastic or reactive nature is controversial and its etiologic agent is human herpes virus type 8 (HHV-8). There are 4 clinical subtypes: classical, epidemic, endemic and iatrogenic.Material and methods: A retrospective review of clinical records and histological preparations of KS cases, diagnosed between January 2001 and December 2013 at the Dermatopathology Department of Hospital Egas Moniz and Centro de Dermatologia Médico-Cirúrgica de Lisboa was made and we assessed differences between the various types.Results: Ninety-one cases were diagnosed, 67.0% of classic KS, 30.8% of epidemic KS; 1.1% of endemic KS and 1.1% of iatrogenic KS. It was found that 85.7% of patients were male and 14.3% were female, and this dominance occurred in all variants. The average age of patients with epidemic KS was lower than the classic variant (37.3 vs 70.0 years, p< 0.001). The lower limbs were the preferred location for all variants (74.2%). Histologically, in patients with classic KS, there was a predominance of the nodule stage (62.3%), while in epidemic KS, plaque was the most common stage (46.4 %) and this difference being almost statistically significant ( p = 0.057). No differences were observed in the various histological stages between classic and epidemic SK.Conclusions: The observed differences in epidemic KS seem to relate more with subtle changes inherent to early lesions rather than only differences of this variant , which is in agreement with the literature.